Evaluation of Intern, Resident and Patient’s KnowledgeOf their Right Charter in Ahvaz Jundishapur University Educational Hospitals - Ahmad Ghorbani; Nasrin Saadati; Nasrin Ayar (Majalah-i ̒ilmī pizishkī-i jundī/shapūr, 2013)
Background and Objective: Provisions of law and medical ethics is one of the principles of patient satisfaction. The hospitals are inseparable units of social medicine which provide services for all the people in the community. In addition, educational hospitals are centers for education and the students acquire experience their. Obeying the laws of community medicine and patients' right charter are unavoidable to provide high quality services, health care and treatment. As follow-up regulatory bodies scattered in the annual evaluation of health service providers, this study was necessary.Subjects and Methods: This cross-sectional study has been done in order to assess patient & interns & resident’s awareness in 2010. The data collection instrument was a questionnaire based on patients' rights provisions. Sampling has been done randomly based on maximum amount of 433 people.Results: Among 433 people, there were 261 visitors, 103 residents, 69 interns, 181 males (% 48.8). The result show that in average %25.5 of visitors and %14.45 of physicians knew nothing about patients right contents, meanwhile %29.8 of visitors and %61.7 of physicians completely knew it.Conclusion: Considering, Ahvaz Jundishapur educational medical university is one of the first rate universities and Ahvaz is one of the developing mega cities; results could be clear lack of good transferring of information or some other reasons which could be suggestible for other studies.